Yaiba : samurai legend. 1 - Aoyama, Gōshō (Shōnen Sandē komikkusu., 2025)
Yaiba Kurogane is an energetic young swordsman who's grown up in the jungle, training to be a samurai with his father, Kenjuro. When they return to Japan, chaos seems to follow wherever Yaiba goes! Destined to be a legendary hero, Yaiba must learn to be a true samurai and save the world! Upon enrolling in school, Yaiba quickly crosses swords with his soon-to-be rival, Onimaru. When Onimaru is transformed into a demon by the cursed power of Fujinken, the Wind God's Sword, Yaiba embarks on a quest to Mount Tengu to find his own enchanted sword. But Yaiba lacks the skill and knowledge to use such a powerful weapon. If he can't control himself, it will control him!